The Impact of Money Market Indicators on Real Estate Finance in Nigeria - Olawande, O.A; EMOH, F. I.; IJASAN, K. C. (Department of Estate Management and Valuation, Faculty of Management Studies and Commerce, 2012)
Money supply in an economy is significantly affected by the money market indicators and, by implication, the funds available to the real estate sector. This study examines the relationship between money supply in the economy and some money market indicators with respect to their impacts on finance for real estate development in Nigeria. Secondary data were obtained from the Central Bank of Nigeria covering five-year study period (2006 to 2010). The Pearson product moment correlation and multivariate regression models were adopted for data analysis. The study found that there is statistically significant relationship between broad money supply (M2) and explanatory variables with P-values < 0.05 except inter-bank call rate (0.7085), and prime lending rate (0.7554). Furthermore, the principal component analysis revealed that interbank call rate, inflation, and monetary policy rates are three components with eigenvalues >1.0; they account for 77.01% of variability in M2. Also, stepwise regression of the variables showed that inflation, monetary policy rate, saving deposit rate, and Treasury bill rate have statistically significant impact on broad money supply in Nigeria. The implication is that money supply in the economy from where funds are made available for real estate development is significantly affected by the indicators and consequently the real estate sector by dwindling financial allocation to the real estate sector. It was recommended that real estate investment trust may possibly be the best option to financing the real estate sector of the Nigerian economy, while the Nigerian Institution of Estate Surveyors and Valuers has great role in birthing the investment vehicle.
Keywords: Real Estate, Monetary Policy, Money Supply, Inflation, Investment Trust, Finance, Property Development